Strategi Pengelolaan Ekosistem Mangrove di Desa Wungkolo Kecamatan Wawonii Selatan Kabupaten Konawe Kepulauan - Muhlis Muhlis; Jamili Jamili; Sitti Wirdhana Ahmad (Jurnal Perencanaan Wilayah, 2019)
This research aimed to describe the composition, structure, mangrove area ecosystem, economic conditions, and social culture as well as to determine the recommended management for mangrove ecosystem. The study was conducted on March-May 2019 in Wungkolo Village. Vegetation sampling used line transect and plot method. Mangrove vegetation data was obtained through observation of each plot for tree strata, saplings and seedlings. Environmental factors and spesies fauna observations were measured at each transect. Economic and socio-cultural data of the community were obtained through interview. Management directives used Analytical Hierarchy Process method. The results showed that mangrove species consists of 10 spesies, including Avicennia lanata, Bruguiera gymnorrhiza, Ceriops tagal, Rhizophora apiculata, Rhizophora mucronata, Rhizophora stylosa, Sonneratia alba, Xylocarpus granatum, Xylocarpus moluccensis and Xylocarpus rumpi. Tree strata mangrove community was dominated by Rhizophora apiculata, saplings strata Bruguiera gymnorrhiza, and seedlings strata Rhizophora apiculata. The mangrove ecosystems area was 574,52 ha, with damaged condition in 2013 compared to 2019. The economic condition of community showed that people's income was still below the standard. The socio-cultural condition of community showed low level of education and knowledge importance of mangrove forests. The recommendation for managing mangrove ecosystems is by maintaining the extent and condition of mangroves, increasing value of mangrove ecosystems and promoting importance of mangrove ecosystems. Keywords: Mangrove, Management Strategies, Wungkolo Village